Actividades de servicio y servitización: oportunidades para una economía circular más sostenible - Pereira Sánchez, Ángeles (2021)
The urgent environmental challenges that society must face in the near future call for a reconsideration of the dominant linear production and consumption model, and a shift to a more circular and sustainable economy. The aim of this paper is to carry out a theoretical-conceptual analysis of the role of service activities, as well the one of services related to production and products, in the dematerialization and greening of the socio-economic system. To this end, a literature review was conducted focusing on three dimensions: firstly, the nature of services and the characteristics that enable the development of a dematerialized economy; secondly, the functional service economy in the framework of a circular economy; and, thirdly, servitization as an innovative business model, based on the hybridization of products and services, with the potential to achieve environmental benefits. Based on the analysis developed, the conclusions section presents a suggested classification of the different service activities with the capacity to support the transition to a more sustainable economy throughout the life cycle of products. A distinction is thus made between different service and servitization activities in the production phase, in the use/consumption phase and in the end-of-cycle recovery phase.